Lactobacillus Protects Against Chronic Suppurative Otitis Media via Modulating RFTN1/ Lipid Raft /TLR4-Mediated Inflammation - Liu Z; Zhang F; Jia F; Li S; Jiang C; Ruan B; Long R (Biologics: Targets & Therapy)
Zhuohui Liu,* Fan Zhang,* Fengfeng Jia, Shuling Li, Chaowu Jiang, Biao Ruan, Ruiqing Long Department of Otolaryngology, The First Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruiqing Long, Department of Otolaryngology, The First Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People’s Republic of China, Email longruiqing@ydyy.cnPurpose: Chronic suppurative otitis media (CSOM) is a prominent contributor to preventable hearing loss globally. Probiotic therapy has attracted research interest in human infectious and inflammatory disease. As the most prevalent probiotic, the role of Lactobacillus in CSOM remains poorly defined. This study aimed to investigate the antipathogenic effects and underlying mechanism of Lactobacillus on CSOM.Methods: RNA sequencing of granulation of middle ear cavity from CSOM patients and lavage fluid of middle ear from normal volunteer was conducted. Human middle ear epithelial cells (HMEEC) and rats infected with Bacillus cereus (B. cereus) and Staphylococcus aureus (S. aureus) were used for CSOM constructing. Western blot, qPCR and Vybrant™ Alexa Fluor™ 488 lipid raft labeling were performed to explore the possible molecular mechanism by which lipid raft linker (RFTN1) regulates lipid raft/toll-like receptor 4 (TLR4). ELISA and HE staining was utilized to evaluate the effect of Lactobacillus on the progression of CSOM in vivo.Results: Based on RNA Sequence analysis, a total of 3646 differentially expressed genes (1620 up-regulated and 2026 down-regulated) were identified in CSOM. RFTN1 was highly expressed in CSOM. Inhibition of RFTN1 not only reduced the inflammatory response of CSOM but also suppressed the formation of lipid rafts. Further investigation revealed that RFTN1 inhibition could reduce the expression of TLR4, which also localizes to the lipid rafts. TLR4 responds to RFTN1-mediated inflammatory responses in CSOM. We treated the CSOM model with Lactobacillus, which has great potential for alleviating the inflammatory response, and found that Lactobacillus attenuated the development of CSOM by reducing RFTN1 and TLR4 expression.Conclusion: In conclusion, these findings suggest a crucial role for Lactobacillus in alleviating CSOM progression and uncovered the molecular mechanism involving Lactobacillus-regulated inhibition of the RFTN1-lipid raft-TLR4 signaling pathway under CSOM conditions.Keywords: CSOM, Lactobacillus, RFTN1, TLR4, S. aureus, B. cereus